Buprenorphine Depresses Respiratory Variability in Obese Mice with Altered Leptin Signaling. (May 2018) - Angel, Chelsea; Glovak, Zachary T.; Alami, Wateen; Mihalko, Sara; Price, Josh; Jiang, Yandong; Baghdoyan, Helen A.; Lydic, Ralph
Abstract : Background: Opiate-induced respiratory depression is sexually dimorphic and associated with increased risk among the obese. The mechanisms underlying these associations are unknown. The present study evaluated the two-tailed hypothesis that sex, leptin status, and obesity modulate buprenorphine-induced changes in breathing. Methods: Mice (n = 40 male and 40 female) comprising four congenic lines that differ in leptin signaling and body weight were injected with saline and buprenorphine (0.3 mg/kg). Whole-body plethysmography was used to quantify the effects on minute ventilation. The data were evaluated using three-way analysis of variance, regression, and Poincaré analyses. Results: Relative to B6 mice with normal leptin, buprenorphine decreased minute ventilation in mice with diet-induced obesity (37.2%; P < 0.0001), ob/ob mice that lack leptin (62.6%; P < 0.0001), and db/db mice with dysfunctional leptin receptors (65.9%; P < 0.0001). Poincaré analyses showed that buprenorphine caused a significant ( P < 0.0001) collapse in minute ventilation variability that was greatest in mice with leptin dysfunction. There was no significant effect of sex or body weight on minute ventilation. Conclusions: The results support the interpretation that leptin status but not body weight or sex contributed to the buprenorphine-induced decrease in minute ventilation. Poincaré plots illustrate that the buprenorphine-induced decrease in minute ventilation variability was greatest in mice with impaired leptin signaling. This is relevant because normal respiratory variability is essential for martialing a compensatory response to ventilatory challenges imposed by disease, obesity, and surgical stress. Abstract : The hypothesis that sex, obesity, and leptin status modulate buprenorphine-induced changes in breathing was tested in male and female normal weight mice and in obese mice with disrupted leptin signaling. Leptin status, but not body weight or sex, contributed to the buprenorphine-induced decrease in minute ventilation variability. Mice with impaired leptin signaling had the largest buprenorphine-induced decrease in minute ventilation variability.